Pt nanowires as electrocatalysts for proton-exchange membrane fuel cells applications: A review - Valério Neto, Edmundo S.; Almeida, Caio V.S.; Colmati, Flávio; Ciapina, Eduardo G. [UNESP]; Salazar-Banda, Giancarlo R.; Eguiluz, Katlin I.B. (Elsevier, 2022)
Due to their high electrocatalytic activity, Pt nanoparticles are widely used as catalysts in low-temperature fuel cells (FCs). However, the high cost and limited supply of Pt boosted the search to enhance its utilization and intrinsic catalytic activity. Recent research shows that Pt and Pt-based nanowires (NWs) fulfill both the possibility of cost reduction and provide surfaces with specific needs. Herein, we review the use of Pt NWs and their alloys as state-of-the-art materials in FC systems. First, several preparation methods of NWs are presented, such as hard-template/templateless, chemical vapor deposition, electrodeposition, pulsed laser ablation, self-assembly, and surfactant/surfactantless synthesis. Next, we discuss their use as anodic materials for methanol and ethanol FCs and cathodic catalysts applied for the oxygen reduction reaction. The morphology of NWs results in materials with preferential exposure of highly active crystal facets, a reduced amount of low coordinated atoms, a high surface aspect ratio, and low charge and mass transport resistances, improving the activity, stability, and durability of catalysts.
Keywords: Cathode; DEFC Anode; Efficiency; Fuel cells; Nanowires; PEMFC